THE PROBLEM OF TIME IN THE ADMINISTRATIVE ACTIVITY OF THE DIRECTOR OF THE PRESCHOOL EDUCATION ORGANIZATION - Akramova Adolatkhan Kodirkhanovna (Western European Studies, 2024)
In the article, proposals and recommendations are put forward on the current issues of the correct distribution of time and its rational use in the management activities of the director of a preschool educational organization. We have presented the analysis of our author's opinions, analyzing the scientific justification of time allocation in the organization of preschool education and the theories in this regard.
Keywords: Preschool education organization; quality; strategy